Vascularized and Innervated Skeletal Muscle Tissue Engineering. Issue 1 (17th October 2019) - Gilbert‐Honick, Jordana; Grayson, Warren
Abstract: Volumetric muscle loss (VML) is a devastating loss of muscle tissue that overwhelms the native regenerative properties of skeletal muscle and results in lifelong functional deficits. There are currently no treatments for VML that fully recover the lost muscle tissue and function. Tissue engineering presents a promising solution for VML treatment and significant research has been performed using tissue engineered muscle constructs in preclinical models of VML with a broad range of defect locations and sizes, tissue engineered construct characteristics, and outcome measures. Due to the complex vascular and neural anatomy within skeletal muscle, regeneration of functional vasculature and nerves is vital for muscle recovery following VML injuries. This review aims to summarize the current state of the field of skeletal muscle tissue engineering using 3D constructs for VML treatment with a focus on studies that have promoted vascular and neural regeneration within the muscle tissue post‐VML. Abstract : Tissue engineered treatments for volumetric muscle loss (VML) span a range of construct compositions, preclinical models, and functional outcomes. Promoting vascular and neural regeneration following VML is vital to ultimate muscle regeneration and function. This review summarizes tissue engineering solutions to VML with a focus on incorporating vascular and neural regenerative components.